The wonder years. Season four - Dinner, Michael, (Director); Stern, Daniel, 1957-; Savage, Fred, 1976-; Lauria, Dan; Mills, Alley (Pueblo, CO : Time Life, 2016)
Kevin Arnold reminisces about his teenage years growing up in his middle-class family in the late 1960s and early 1970s.
Growing up -- Ninth grade man -- The journey -- The cost of living -- It's a mad, mad, Madeline world -- Little Debbie -- The ties that bind -- The sixth man -- A very Cutlip Christmas -- The candidate -- Heartbreak -- Denial -- Who's Aunt Rose? -- Courage -- Buster -- Road trip -- When worlds collide -- Separate rooms -- The yearbook -- The accident -- The house that Jack built -- Graduation -- The wonder years.
Dolby digital stereo, full screen 1.33:1.
Features: featurettes, interviews.
Fred Savage, Dan Lauria, Alley Mills, Danica McKellar, Josh Saviano.
Originally broadcast on television 1990-1991.
TV rating: TV-PG.
Closed-captioned.
Keywords: Teenagers -- Drama; Families -- Drama; Coming of age -- Drama; Television series; Fiction television programs; Video recordings for the hearing impaired; Comedy television programs